COST MANAGEMENT CONCEPT AND PROJECT EVALUATION METHODS - Aničić, Dušan; Aničić, Jugoslav (Journal of process management and new technologies, 2019)
The organizations which accepted project management concept among the first, gained a lot of advantages compared to others, such as: faster and easier adjustment to the environment, shorter accomplishment time, structured decision-making, responsibility specification, customer needs focus, etc. One of the basic factors of project management is costs because they demand fund allocation for its realization. Project management is a complex process, with business environment complexity in mind. Therefore, the issues of selection, realization and evaluation of the project deserve significant attention. The aim of this paper is to indicate project management concept advantages, the importance of project cost estimate and control, as well as evaluation method and project selection with the aim of efficiency increase for the entire process.